2022 RECAP. SEE YOU IN 2023 - Hanisah, Kasbon; Wan Noor Farah, Wan Shamsuddin; Nor Yazi, Khamis; Farah Liyana, Ahmad Azmey (Pusat Bahasa Moden (PBM), 2022)
2022 finds us opportunities and challenges, yet we committed ourselves to fight a good fight in our lives. At the Centre for Modern Languages (CML), thanks to the dedication, support and passion of all academicians, administrators and the technical team, everything was made possible. 2022 has been a great year, and here are some of the amazing chapters captured through the lens.